(untitled) (Research, Society and Development, 2022)
The objective of this article is to analyze the attractiveness of an unplanned cluster of health services, from the perspective of cluster theory and the marketing mix (product, price, place, promotion, processes, people and physical evidence). To achieve this purpose, it was decided to produce an exploratory research, of a quantitative nature, through interviews with closed questions, carried out with users of health services, in Aracaju, Sergipe. Logistic regression was chosen to analyze the research data and the IBM SPSS software was used to process the data. The results of the study showed that of the seven constructs, components of the service marketing mix, only two are not considered relevant to the attractiveness of the researched cluster: promotion and people. The study serves as a guideline for managers of companies that belong to these clusters to develop strategies appropriate to their reality, thus obtaining a competitive advantage over their competitors.